Comparison of a New Radiographic Technique with MRI Measurements for Tibial Tunnel Evaluation in ACL Reconstruction - Mücahid Osman Yücel; Raşit Emin Dalaslan; Sönmez Sağlam; Zekeriya Okan Karaduman; Mehmet Arıcan; Bedrettin Akar; Volkan Tural (Diagnostics)
Background/Objectives: The correct angular placement of the tibial tunnel is crucial to ensure graft tension, maintain knee stability, and ensure optimal clinical outcomes after anterior cruciate ligament (ACL) reconstruction. While 3D imaging methods such as MRI and CT are the gold standard for evaluating tunnel positioning, their routine use is limited by cost, availability, and time constraints. In clinical practice, 2D radiographs are more accessible but lack established reliability in accurately estimating tunnel angles. The aim of this study was to convert 2D radiographic angular measurements used in the evaluation of patients undergoing anterior cruciate ligament reconstruction into 3D values with a simple method and to compare these measurements with three-dimensional angles calculated using conventional MRI and CT. Methods: This retrospective study included 38 patients who underwent anatomic anterior cruciate ligament reconstruction. Postoperative radiographs and MR images were analyzed to determine the tibial tunnel angles. The angles calculated from 2D radiographs were statistically analyzed for their correlation with the actual 3D angles measured by MRI. Results: The analysis showed a strong correlation between tibial tunnel angles from radiographs and MRI, with minimal, non-significant differences. This suggests that radiographs can provide a reliable estimate of tibial tunnel angles. Conclusions: These findings suggest that radiographs can predict tibial tunnel angles in ACL reconstruction as accurately as MRI. This method can guide the correct tunnel angle and facilitate postoperative evaluation. Further studies are needed to confirm these results across various populations and techniques.